DENSIDADE POPULACIONAL E SEUS EFEITOS SOBRE OS CARACTERES DA ESPIGA EM MILHO - Bosa, Diogo; Valentini, Ana P. F.; Gaviraghi, Fernando; Martins, João A. K.; Zambonato, Felipe; Wagner, Juliano F.; Battisti, Gabriel K.; Migliorini, Guylherme; Fronza, Rafael; Berto, Jorge; et al. (Salão do Conhecimento, 2013)
Resumo